The Outcome of Primary Hyperaldosteronism in Resistant Hypertension with Efficiency Cost in Clinical Practices A Case Report - Raharjo, Fajar Maulana; Lil Alamin, Rahmatan; Gunawan, Michelle; Nur Samsu (Universitas Brawijaya, 2025)
Aldosterone as a major mineralocorticoid has an important role in regulating circulating volume and potassium homeostasis, especially in the kidney. Manifestation of hypertension and hypokalemia in the young age population must be considered about the role of Aldosterone. This case report will discuss a patient with uncontrolled hypertension with severe hypokalemia who was treated with 3 kinds of antihypertensive drugs but the blood pressure is still high. After performing several diagnostic tests, the Aldosterone level was significantly high and left an adrenal tumor from an abdominal MRI. The patient treated with mineralocorticoid receptor antagonists or Spironolactone 25mg daily and show controlled blood pressure.